Jihadist Salafism in Türkiye: The Ideology of Abu Hanzala (Halis Bayancuk) - Ramazan Akkır (Marifetname)

(untitled)
This study explores Jihadist Salafism within Salafist Islam, characterized by its adherence to early Islamic practices and interpretations, advocating extreme and often violent approaches, including armed struggle, to achieve ideological objectives, deviating from mainstream Salafist principles. Despite considerable research on Salafism, understanding within the Turkish context remains limited. Salafist ideology in Turkey emerged in the 1980s, gaining momentum post-9/11 and peaking during the Syrian civil war. Focusing on Halis Bayancuk (Abu Hanzala), a prominent figure in Turkish politics and founder of the Tawhid and Sunnah Community, known for his strict adherence to Salafist principles, this study meticulously analyzes his ideology, intertwined with a deep exploration of jihad principles. Using Quintan Wiktorowicz’s framework, Salafists are categorized into purists, politicos, and jihadists. The research aims to uncover nuances and insights about Salafist ideology in Turkey by employing document analysis. It uses discourse analysis to study Abu Hanzala’s religious and political views, aiming to provide a detailed understanding of Salafism’s complex structure in Turkey and its manifestation in the socio-political landscape.